Acute kidney injury as a predictor of poor outcome post cardiopulmonary bypass in children - Alam, Shahzad; Shalini, Akunuri; Hegde, Rajesh; Mazahir, Rufaida (International Journal of Contemporary Pediatrics, 2016)
Background: We objective of the current study was to identify the prevalence of AKI and classify them based on Acute Kidney Injury Network (AKIN) staging system. We also evaluated the outcome of patients developing AKI and identified the associated risk factors. Methods: This retrospective study was conducted in pediatric cardiac ICU of a tertiary care hospital. Patient < 18 years who underwent cardiac surgery on cardiopulmonary bypass (CPB) for congenital heart disease were enrolled in the study. AKI was defined as increase in serum creatinine ≥ 0.3 mg/dl within 48 hours or 1.5 times or more from baseline within the first 7 days post-surgery. Results: Nine hundred and twenty children were enrolled in the study. Three hundred and twelve (34%) children developed AKI with 202 (20%) developing stage I, 92 (10%) stage II and 18 (2%) stage III. Resolution was achieved in all the patients and none developed chronic kidney disease. Risk factors for AKI were higher CPB time, higher aortic cross clamp time, significant arrhythmias and higher inotropic requirement at admission. Children with stage 2 and 3 disease had higher odds for requirement of mechanical ventilation > 24 hours and > 72 hours, length of ICU stay > 5 days and in hospital mortality. Conclusions: AKI following cardiac surgery is common. Although majority of the cases are mild disease and self-limiting it can significantly affect the outcome of these patients.